2001
DOI: 10.1007/s003840100325
|View full text |Cite
|
Sign up to set email alerts
|

Anorectal sphincter function and rectal barostat study in patients following transanal endoscopic microsurgery

Abstract: Background and aims: This study evaluated the effect of transanal endoscopic microsurgery (TEM) on anorectal sphincter functions and determined the risk factors for anorectal dysfunctions (including incontinence). Patients and methods: A study group of 33 patients with small, mobile rectal tumors (adenoma and carcinoma) located up to 12 cm from the anal verge underwent anorectal motility studies (using pull-through anorectal manometry and rectal barostat) and endoanal ultrasound prior to surgery and 3 weeks an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
90
5
5

Year Published

2008
2008
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(110 citation statements)
references
References 10 publications
7
90
5
5
Order By: Relevance
“…Specifically, there are several studies that have looked at functional outcomes after TEM, given that it entails a large, rigid rectoscope inserted through the anus for a prolonged period of time. In a small prospective study, Herman et al 56 assessed the risk factors for anorectal dysfunction after TES and found that ~50% of their patients had disturbances in anorectal function at 3 weeks, with partial-to-moderate dysfunction in 21% at 6 months after TES. The most common risk factors were preoperative disturbances in anorectal function, pre-or postoperative abnormalities on endoanal ultrasound, and the extent of excision of the lesion (lesions that were >50% of the circumference and full-thickness excisions).…”
Section: Outcomes Functionalmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, there are several studies that have looked at functional outcomes after TEM, given that it entails a large, rigid rectoscope inserted through the anus for a prolonged period of time. In a small prospective study, Herman et al 56 assessed the risk factors for anorectal dysfunction after TES and found that ~50% of their patients had disturbances in anorectal function at 3 weeks, with partial-to-moderate dysfunction in 21% at 6 months after TES. The most common risk factors were preoperative disturbances in anorectal function, pre-or postoperative abnormalities on endoanal ultrasound, and the extent of excision of the lesion (lesions that were >50% of the circumference and full-thickness excisions).…”
Section: Outcomes Functionalmentioning
confidence: 99%
“…Nevertheless, functional issues were temporary and appeared worse in patients with the aforementioned risk factors. 56 . Jin et al 57 assessed 37 patients who underwent TEM for rectal tumors, including adenomas and carcinomas.…”
Section: Outcomes Functionalmentioning
confidence: 99%
“…The studies report contradictory results. Some demonstrated a temporary effect on anorectal function [36,37], but others reported preserved function after TEM [38][39][40]. In order to evaluate the functional outcomes, we used two scales (FIQoLS and Wexner score).…”
Section: Tech Coloproctolmentioning
confidence: 99%
“…Regarding the effect of a prolonged anal dilatation with the 40 mm diameter TEM operative rectoscope, manometric studies indicate a decrease in anal sphincter tone ranging from 25% to 37% of pre-operative sphincter pressure, with recovery to clinical continence within 6-16 weeks (Herman et al, 2001). We observed postoperative transitory grade II incontinence in 65 of the 100 patients, with full recovery in 98% of the cases after 12 weeks.…”
Section: Tem For Benign Lesionsmentioning
confidence: 99%